An emergy-based evaluation of a reverse logistics network for steel recycling - Giannetti, Biagio F. [UNESP]; Bonilla, Silvia H. [UNESP]; Almeida, Cecilia M. V. B. [UNESP] (Elsevier B.V., 2013)
Efficient implementation of recycling networks requires appropriate logistical structures for managing the reverse flow of materials from users to producers. The steel sheet distributor studied had established a protocol for scrap recovery with the steel plant and its customers. The company invested in producing containers, hiring a specialized labor force and in purchasing trucks for container transportation to implement the logistics network for recycling. That network interconnected the company with two kinds of customers: the ones returning scrap and the ones who preferred to continue business-as-usual. The logistical network was analyzed using emergy synthesis, and the data obtained were used to evaluate and compare the system's environmental costs and benefits from the perspective of the distributor and the steel plant operator. The use of emergy ternary diagrams provided a way to assess recycle strategies to compare the relative economic and environmental benefits of the logistical network implemented. The minimum quantity of scrap that the distributor must recover to improve environmental benefits was determined allowing decision on whether it is worth keeping the system running. The new assessment method proposed also may help policy-makers to create strategies to reward or incentive users of reverse logistics, and help to establish regulations, by decreasing taxes or stimulating innovation, for effectively implement the National Policy on Solid Waste. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Emergy synthesis; Reverse logistic network; Environmental; Economic benefits